DEVICE FOR MONITORING THE CONDITION OF THE NATURAL BACKGROUND (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Life on Earth arose and exists in terms of natural ionizing radiation. Environmental pollution with radioactive substances begins with the emergence of the nuclear industry. Proceeding from the accepted truth that there is no safe dose of exposure to radioactive radiation and accumulated over the years experience (more than 25 years), the author of this article provides an apparatus for monitoring the condition of the natural radiation background based on light and sound indication in all cases when there is increase toward “imperturbable” atmosphere.